NUMSA's Socially Owned Renewable Energy Proposal (2012) in Response to the Green Economy Discourse: A Critical Discourse Analysis - French, Lara (Department of Sociology, 2024)
In 2012 the National Union of Metalworkers of South Africa (NUMSA) published their 9th National Congress Final Economic Resolutions” (2012) which included a resolution of their proposal on ‘Building a Socially Owned Renewable Energy Sector in SA'. This proposal was primarily in response to the South African government's 2010 Integrated Resource Plan (IRP) which set out a twenty-year plan to increase South Africa's renewable energy sources through public-private partnerships. The South African government's IRP and its emphasis on privatisation, green technology and green jobs can be seen as an expression of the South African government's adoption of the neoliberal green economy discourse. The problem that this research analyses is: in what ways could NUMSA's 2012 alternative proposal on socially owned renewable energy address South Africa's green economy response? This research uses a critical discourse analysis (CDA) understanding of discourse analysis where the content of discourses is not the predominant focus but also significant is the ways in which discourse manifests and interacts with social power relations and how this results in inequality and the dominance of certain groups of people over others. This research likewise does not simply describe the South African government's green economy discourse but also exposes the power relations behind it and in doing so assert the need for alternatives such as NUMSA's proposal. The research uses CDA to position NUMSA's alternative proposal of socially owned renewable energy within NUMSA's rejection of the green economy discourse as well as their interpretation of the just transition discourse. The research uses J.W. Moore's theory of the Capitalocene as a conceptual framework. It uses the Capitalocene to critique the way in which the IRP and the green economy discourse, as well as NUMSA's proposal, contain within them productivist thinking. The research goes on to show that NUMSA's proposal for socially owned renewable energy as a response to the South African government's renewable energy policy is based on the alternative theories such as ecosocialism and energy democracy. It concludes with using the Capitalocene's relational thinking, as well as degrowth and postwork, to show that there is a need for more transformative thinking in NUMSA's proposal for a socially owned renewable energy sector.